Characterization of aerosol photooxidation flow reactors: heterogeneous oxidation, secondary organic aerosol formation and cloud condensation nuclei activity measurements - A. T. Lambe; A. T. Ahern; L. R. Williams; J. G. Slowik; J. P. S. Wong; J. P. D. Abbatt; W. H. Brune; N. L. Ng; J. P. Wright; D. R. Croasdale; D. R. Worsnop; P. Davidovits; et al. (Atmospheric Measurement Techniques, 2011)
Motivated by the need to develop instrumental techniques for characterizing organic aerosol aging, we report on the performance of the Toronto Photo-Oxidation Tube (TPOT) and Potential Aerosol Mass (PAM) flow tube reactors under a variety of experimental conditions. The PAM system was designed with lower surface-area-to-volume (SA/V) ratio to minimize wall effects; the TPOT reactor was designed to study heterogeneous aerosol chemistry where wall loss can be independently measured. The following studies were performed: (1) transmission efficiency measurements for CO2, SO2, and bis(2-ethylhexyl) sebacate (BES) particles, (2) H2SO4 yield measurements from the oxidation of SO2, (3) residence time distribution (RTD) measurements for CO2, SO2, and BES particles, (4) aerosol mass spectra, O/C and H/C ratios, and cloud condensation nuclei (CCN) activity measurements of BES particles exposed to OH radicals, and (5) aerosol mass spectra, O/C and H/C ratios, CCN activity, and yield measurements of secondary organic aerosol (SOA) generated from gas-phase OH oxidation of m-xylene and α-pinene. OH exposures ranged from (2.0 ± 1.0) × 1010 to (1.8 ± 0.3) × 1012 molec cm−3 s. Where applicable, data from the flow tube reactors are compared with published results from the Caltech smog chamber. The TPOT yielded narrower RTDs. However, its transmission efficiency for SO2 was lower than that for the PAM. Transmission efficiency for BES and H2SO4 particles was size-dependent and was similar for the two flow tube designs. Oxidized BES particles had similar O/C and H/C ratios and CCN activity at OH exposures greater than 1011 molec cm−3 s, but different CCN activity at lower OH exposures. The O/C ratio, H/C ratio, and yield of m-xylene and α-pinene SOA was strongly affected by reactor design and operating conditions, with wall interactions seemingly having the strongest influence on SOA yield. At comparable OH exposures, flow tube SOA was more oxidized than smog chamber SOA, possibly because of faster gas-phase oxidation relative to particle nucleation. SOA yields were lower in the TPOT than in the PAM, but CCN activity of flow-tube-generated SOA particles was similar. For comparable OH exposures, α-pinene SOA yields were similar in the PAM and Caltech chambers, but m-xylene SOA yields were much lower in the PAM compared to the Caltech chamber.